(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the psychological empowerment of kindergarten principals, and to identify the significance of the differences in psychological empowerment among kindergarten principals according to specialization and length of service. (1995), as the researcher prepared (26) paragraphs distributed on (4) dimensions (meaning, efficiency, self-report and impact), and the researcher verified the apparent validity of the psychological empowerment scale and the consistency of its paragraphs, and calculated its stability by re-testing, as the reliability coefficient reached (0.80). , and by the Facronbach method, it amounted to (0.84), and the researcher applied the scale to the research sample of (159) principals from the directorates of kindergartens in the governorate of Baghdad in its six districts. The sample was chosen in a simple random way. The researcher came to the following results: Kindergarten principals have psychological empowerment, there are no statistically significant differences in the variables of specialization and length of service for kindergarten principals in psychological empowerment as well as There is no effect of interaction between specialization and length of service.